STRATEGY OF THE OPTIMAL CHOICE OF THE SHARE PRICE ON THE STOCK EXCHANGE - Aleksey Karavanov (Вестник Северо-Кавказского федерального университета)
The paper discloses a method for determining the maximum number of with a probability of more than 1/3 of the plurality of unknown numbers arriving in sequence without the possibility of returning to the previous one. This study has practical value for the participants of the stock exchanges. For example, to determine the maximum share price for a certain period of time to more profitable its sales. This strategy can also be used to select the minimum price (purchase) of shares, which can significantly increase the financial result of the game in the stock exchange.